Impact of a Cylinder Against a Rigid Target. Part II. Initial Condition. - Nowińska, A.; Kosiński, W. (Engineering Transactions, 1996)
An analysis of widely known Taylor's experiment that concerns the impact of short deformable cylinders made of a rigid-viscoplastic material against the rigid target, is performed. The case of axi-symmetric geometry with finite deformations and radial inertia is considered. The velocity initial condition given by the jump of the vertical component of the field does not belong to the problem solution as the equations describing the problem do not permit the first order discontinuity. To create the procedure initiating a numerical algorithm for this impact problem, the idea of a thin viscoplastic layer is introduced and a parametric approximation of the velocity field in a power form is proposed. The velocity field obtained from the approximation approches for t → t0 the profile characteristic for the viscoplastic model.